First Taste of Freedom : A Cultural History of Bicycle Marketing in the United States - Turpin, Robert J. (Book collections on Project MUSE., 2018)
"First Taste of Freedom" is a work of American cultural history focused on the bicycle market in the United States. A primary goal of the research was also to understand how the bicycle can be seen so differently in the US as opposed to other countries"--